A new species of nurse-frog (Aromobatidae, Allobates) from the Amazonian forest of Loreto, Peru - Gagliardi-Urrutia, Giussepe; Castroviejo-Fisher, Santiago; Rojas-Runjaic, Fernando J. M.; Jaramillo, Andrés F.; Solís, Samantha; Simões, Pedro Ivo (Zootaxa, 2021)
We describe a new species of nurse-frog (Aromobatidae, Allobates) from the Amazonian forest of Loreto, Peru using morphological, acoustic and genetic data. Our phylogenetic analysis placed Allobates sieggreenae sp. nov. as the sister species of A. trilineatus, the most similar-looking species and with which it was previously confused. However, the new species has a brown dorsum, solid dark brown lateral dark stripe not fading towards groin, adult males with few and sparse melanophores over a cream background on chin, chest, and belly, dark transverse bars absent on thighs, and an advertisement call formed by a trill of single notes (in A. trilineatus dorsum dark brown, blackish brown lateral dark stripe, paler from mid-body to groin, adult males with a dark background color on chin, chest, and belly due to a dense layer of melanophores, dark transverse bar present on dorsal surface of thighs, and trills of paired notes). Allobates sieggreenae is known from two localities of Amazonian white-sand forest ecosystems east of the Ucayali River.